2004
DOI: 10.4049/jimmunol.173.5.2968
|View full text |Cite
|
Sign up to set email alerts
|

Presumptive Lymph Node Organizers are Differentially Represented in Developing Mesenteric and Peripheral Nodes

Abstract: During murine embryogenesis, the formation of Peyer’s patches (PPs) is initiated by CD45+CD4+CD3− lymphoid tissue inducers that trigger adhesion molecule expression and specific chemokine production from an organizing stromal cell population through ligation of the lymphotoxin-β receptor. However, the steps involved in the development of lymph nodes (LNs) are less clear than those of PPs, and the characteristics of the organizing cells within the LN anlagen have yet to be documented. In this study, we show for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
120
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 110 publications
(128 citation statements)
references
References 33 publications
8
120
0
Order By: Relevance
“…This is supported by the fact that, upon transgenic overexpression of TRANCE in hemopoietic cells of the TRANCE Ϫ/Ϫ mice, numbers of LTi cells increase, resulting in the formation of several lymph nodes (16). During embryonic development, TRANCE expression is found on LTi cells, but most notably on stromal cells within the developing lymph nodes (2,16). Local production of TRANCE, together with the findings that PPs develop normally in the absence of TRANCE, implies that TRANCE acts locally by either attracting or differentiating LTi cells.…”
Section: Generation Of Functional Lti Cellssupporting
confidence: 49%
See 3 more Smart Citations
“…This is supported by the fact that, upon transgenic overexpression of TRANCE in hemopoietic cells of the TRANCE Ϫ/Ϫ mice, numbers of LTi cells increase, resulting in the formation of several lymph nodes (16). During embryonic development, TRANCE expression is found on LTi cells, but most notably on stromal cells within the developing lymph nodes (2,16). Local production of TRANCE, together with the findings that PPs develop normally in the absence of TRANCE, implies that TRANCE acts locally by either attracting or differentiating LTi cells.…”
Section: Generation Of Functional Lti Cellssupporting
confidence: 49%
“…3). First, the mesenchymal cells differentiate toward stromal cells that produce TRANCE (2), and perhaps at this point are also induced to express LT␤R and TNFR. Second, triggering of LT␤R leads to the up-regulation of adhesion molecules, such as VCAM-1, and the production of chemokines.…”
Section: The Earliest Eventsmentioning
confidence: 99%
See 2 more Smart Citations
“…They have been implicated in lymphocyte recruitment from the bloodstream [2][3][4], the structural compartmentalization of T-B microdomains [5][6][7] and T-B cell interactions within the tissue [8]. Recent studies have demonstrated that the same chemokines (CK) are required for the embryonic development and organization of the majority of secondary lymphoid organs [9], being produced by a subset of mesenchymal cells (VCAM-1 + LTbR + , "organizers") in the early lymphoid anlagen [10,11]. It has been suggested that these CK contribute to the clustering of the earliest wave of hematopoietic cells (CD3 -CD4 + LTb + , "inducers"), preceding peripheral node addressin (PNAd) + high endothelial venule (HEV) formation, T-B lymphocyte compartmentalization and follicular dendritic cell (FDC) network development [12].…”
Section: Introductionmentioning
confidence: 99%